(3EMcGe GdCMcGe aj TQM CMGOjK SjO GdCfGes - (3Jbi GdOjf GHf Objb GdYjOs ((3GdbGgQI GdeMQhSI s)
(3ChdgG (B:s
(3hHYO aEfg deG cGf GdYde CTQa eG Ndb ai GdhLhO aGNJQJ GdcJGH GdeYQha HGdYeOI ddEeGe GdMGaX YHO GdZfi cJGH GdWgGQI s
(3BNQgG (B:s
(3ceG jbhd eGdc QMeg dGdg ai LhGR HjYg ai GdOjf Ydi GdJaUjd ai ePgHg , hePgH GdTGaYi Je TQM YeOI GdCMcGe s
(3HChdgG hBNQgG SeGYGJ hbQGAGJ MOjKIs
(3cJHJ GdYfGhjf HGdMeQIs
(3hajgG bdjd ef GdChQGb HNW eZGjQ s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs